Regional Anesthesia as a Safe Alternative to General Anesthesia in the Multiple-trauma Patient. Issue 1 (January 1981) - Butler, Stephen H.; Freund, Peter R.
Abstract : The safety and effectiveness of selected nerve blocks to provide protracted anesthesia was demonstrated in a multiple-trauma patient requiring complex surgical repair.